Pitch Lake, Trinidad, W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
This is an aerial view of the pitch lake at Brighton, La Brea, south west Trinidad. In the foreground we envisage mining operations are in progress as there are buildings, vehicles and equipment in this area. In mid-ground is the natural pitch lake itself, with numerous pools of rainwater forming patterns on its surface. Beyond the pitch lake there are trees, vegetation, buildings in the distance, a squat cylindrical oil storage tank, oil derricks faintly visible and the sea. Postcard number DT-77843-B.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Brighton; Cities and towns--Trinidad and Tobago--La Brea; Asphalt industry--Trinidad and Tobago; Pitch; Oil storage tanks--Trinidad and Tobago; Buildings--Trinidad and Tobago; Trinidad and Tobago--Aerial Views; Seas--Trinidad and Tobago; [1935]; Pitch Lake, The (La Brea)